Prevalence of Hypovitaminosis D and its Association with Serum Lipids in Patients with Type 2 Diabetes Mellitus - Yadav, Naval Kishor; Dhakal, Sarita; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2024)
Background Hypovitaminosis D has become worldwide public health concern affecting all age groups and both genders. Its prevalence is very high in South Asia. Many studies reported that vitamin D deficiency is concerned with diabetes mellitus and impaired glucose tolerance. The aim of this research was to find the prevalence of hypovitaminosis D and its association with serum lipids among type 2 diabetic patients. Methods A cross-sectional study, conducted among a total 162 patients with type 2 diabetes mellitus in Manipal Teaching Hospital, Pokhara. The serum level of FBS, PPBS, urea, creatinine, calcium and phosphorus, HbA1c, TG, TC, HDL-C, and vitamin D levels were measured. In the descriptive categorical data were reported in frequency with percentage and numerical data were presented as mean±SD while in inferential statistics to compare the value student t-test were used. p-value<0.05 was considered as statistically significant. Results The mean±SD serum level of vitamin D was 24.48 ± 13.21 ng/mL in patients with type 2 diabetes. The prevalence of hypovitaminosis D was 69.14% (With 95% CI as 62.02 to 76.25%) and sufficient of vitamin D in 30.86% (With 95% CI as 23.74% to 37.97%) among patients with type 2 diabetes. The serum lipids showed statistically insignificant association between hypovitaminosis D with sufficient of vitamin D. Conclusions This research showed that only in one third of the patients had Vitamin D sufficiency. The serum lipids were slightly increased in patients who had hypovitaminosis D.